Perancangan Interior Galeri Kopi Rollaas di Surabaya - Carmelia Devina (Intra, 2017)
The design on this coffee gallery came from the unawareness of Indonesian people based on Indonesian coffee facts, In which case Indonesia is one of the biggest coffee producers beside Brazil and Columbia. Coffee has a big potential to grow in Indonesia, but this potential cannot be maximized (due to) unawareness of Indonesian people on the quality of Indonesian coffee, In fact, Indonesian coffee has a good quality , therefore Indonesian people need a mediation to learn more about the fact of Indonesian coffee and its quality.                With a proper mediation, Indonesian people will more interest with the local coffee product than the import products, and Indonesian people also can appreciate it better, thus the image of Indonesian coffee can be leveraged and be at top of their mind compared to the imported coffee products, also the Indonesian people will realize the high potential of Indonesian coffee that will bring a positive impact to the Indonesian economic condition.